Pengaruh Daya Saing dan Kualitas Produk Kecantikan terhadap Loyalitas Konsumen Produk Scarlett di Bandung - Evita Septiyani; Prihartono Aksan Halim (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was proposed to understand how much influence the competitiveness and quality of beauty products on consumer loyalty of Scarlett products in Bandung City. The method used in this study was qualitative research by giving questionnaires before and after to 308 people and taking 30 people to be used as variable samples. This study used non-probability samples selected using purposive sampling techniques. The results of this study show that competitiveness has a significant influence on repurchase interest by 42% while 58% is influenced by other variables. And the results of the study of product quality have a significant influence on consumer loyalty in repeat purchase interest by 72.1% while 27.9% is influenced by other variables.